Systematic Review: Perkembangan Penelitian Hutan Kota di Indonesia Tahun 2000-2024 - Rachmad Hermawan; Arif Kurnia Wijayanto; Ario Vallentino Syahgatra; Luthfia Ainur Rahma (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to analyze the development of urban forest research themes in Indonesia from 2000-2024. The method used is a systematic literature review with the scholar.google.com site and VOSviewer software. The articles reviewed in the research were 150 articles. The results showed that the number of articles tended to increase from 2000 to 2024 with the highest increase occurring in 2010. The most commonly used terms in research are hutan kota and urban forests. Most of the research was conducted in the provinces of West Java, DKI Jakarta, and East JavaThe most frequently used research method was field observation, followed by survey/interview methods and field measurements. In conclusion, the most common article themes were physical and biotic with the most subthemes being biodiversity conservation, while the subthemes for which no articles were found were water management, healing, tree prices, and stakeholders. Keywords: Urban Forests, Research, Developments, Green Open Spaces, Systematic Reviews